Comparison of feasibility and results of frailty assessment methods prior to left ventricular assist device implantation. (6th January 2022) - Roehrich, Luise; Sündermann, Simon H.; Just, Isabell Anna; Kopp Fernandes, Laurenz; Stein, Julia; Solowjowa, Natalia; Mulzer, Johanna; Mueller, Marcus; Hummel, Manfred; Knierim, Jan; Potapov, Evgenij; Falk, Volkmar; et al.
Abstract: Aims: Assessing frailty and sarcopenia is considered a valuable cornerstone of perioperative risk stratification in advanced heart failure patients. The lack of an international consensus on a diagnostic standard impedes its implementation in the clinical routine. This study aimed to compare the feasibility and prognostic impact of different assessment tools in patients undergoing continuous‐flow left ventricular assist device (cf‐LVAD) implantation. Methods and results: We prospectively compared feasibility and prognostic values of six frailty/sarcopenia assessment methods in 94 patients prior to cf‐LVAD implantation: bioelectrical impedance analysis (BIA), computed tomography (CT)‐based measurement of two muscle areas/body surface area [erector spinae muscle (TMESA/BSA) and iliopsoas muscle (TPA/BSA)], physical performance tests [grip strength, 6 min walk test (6MWT)] and Rockwood Clinical Frailty Scale (RCFS). Six‐month mortality and/or prolonged ventilation time >95 h was defined as the primary endpoint. BIA and CT showed full feasibility (100%); physical performance and RCFS was limited due to patients' clinical status (feasibility: 87% grip strength, 62% 6MWT, 88% RCFS). Phase angle derived by BIA showed the best results regarding the prognostic value for 6 month mortality and/or prolonged ventilation time >95 h (odds ratio (OR) 0.66 [95% confidence interval (CI): 0.46–0.92], P  = 0.019; area under the curve (AUC) 0.65). It provided incremental value to the clinical risk assessment of EuroSCORE II: C‐index of the combined model was 0.75 [95% CI; 0.651–0.848] compared with C‐index of EuroSCORE II alone, which was 0.73 (95% CI: 0.633–0.835). Six‐month survival was decreased in patients with reduced body cell mass derived by BIA or reduced muscle area in the CT scan compared with patients with normal values: body cell mass 65% (95% CI: 51.8–81.6%) vs. 83% (95% CI: 74.0–93.9%); P  = 0.03, TMESA/BSA 65% (95% CI: 51.2–82.2%) vs. 82% (95% CI: 73.2–93.0%); P  = 0.032 and TPA/BSA 66% (95% CI: 53.7–81.0%) vs. 85% (95% CI: 75.0–95.8%); P  = 0.035. Conclusions: Bioelectrical impedance analysis parameters and CT measurements were shown to be suitable to predict 6‐month mortality and/or prolonged ventilation time >95 h in patients with advanced heart failure prior to cf‐LVAD implantation. Phase angle had the best predictive capacity and sarcopenia diagnosed by reduced body cell mass in BIA or muscle area in CT was associated with a decreased 6 month survival.